Influence of non-enzymatic glycation on the mechanical properties of cortical bone. (July 2021) - Jia, Shaowei; Gong, He; Cen, Haipeng; Shi, Peipei; Zhang, Rui; Li, Zhaowei; Bi, Xuewei
Abstract: Poor bone quality induced by non-enzymatic glycation (NEG) of bone tissue in patients with type 2 diabetes mellitus (T2DM) is regarded as the major factor of bone fragility and affecting bone mechanical properties. A comprehensive and systemic mechanical investigation for evaluating the effect of NEG on bone was still lacking. In order to provide additional information for the bone quality of T2DM, the effects of NEG on mechanical properties of cortical bone were investigated in terms of elastoplasticity, fracture toughness and viscoelasticity. All samples of cortical bone, including the samples of strength test (n = 20), fracture toughness test (n = 40, quasi-static and fall-like conditions with displacement rates of 10 −3 mm/s and 10 mm/s, respectively) and stress relaxation test (n = 20), were harvested from bovine tibiae. The samples of each test were equally divided into incubated-control group and ribose-incubated group. All mechanical tests were performed after incubating all samples for 15 days. Post-yield strain (p = 0.014), post-yield energy (p < 0.0001) and damage fraction (p = 0.040) of ribose-incubated group were significantly lower than those of incubated-control group, but secant modulus (p = 0.029) of ribose-incubated group was significantly higher than that of incubated-control group. In quasi-static condition, the plastic contribution J pl of fracture toughness (p = 0.043) of ribose-incubated group was significantly lower than that of incubated-control group. In fall-like condition, there were no differences in J pl, elastic contribution J el and J- integral in both two groups. The quasi-static J el (p < 0.0001, p < 0.0001) of incubated-control and ribose-incubated groups and J- integral (p = 0.007) of incubated-control group were all significantly higher than those of fall-like condition. In stress relaxation test, initial modulus E 0 (p = 0.040) and equilibrium modulus (p = 0.029) of ribose-incubated group were significantly higher than those of incubated-control group. Reductions of relaxation modulus, which were the differences between two adjacent time points within 700 s–3000 s for ribose-incubated group, were significantly lower than those of incubated-control group. NEG could decrease the post-yield properties and quasi-static facture toughness of cortical bone, especially the plastic contribution of quasi-static fracture toughness. It could also decrease the viscoelasticity of cortical bone. The present study confirmed the negative effects of NEG on the mechanical properties of cortical bone in terms of elastoplasticity, fracture toughness and viscoelasticity, but NEG had no significant effect on the fracture toughness of cortical bone at fall-like loading. These results provided more evidence for increased fragility of cortical bone in patients with T2DM. Graphical abstract: Image 1 Highlights: NEG could decrease the post-yield properties and damage fraction of cortical bone. NEG could reduce plastic contribution of J -integral of cortical bone under quasi-static situation. Under fall-like situation, NEG had no significant effect on J -integral of cortical bone. NEG could also decrease the viscoelasticity of cortical bone.